2023
DOI: 10.3389/fpubh.2023.1003923
|View full text |Cite
|
Sign up to set email alerts
|

The infected and the affected: A longitudinal study of the impact of the COVID-19 pandemic on schoolchildren in Florida

Abstract: ObjectivesTo identify risk factors associated with symptoms of anxiety, depression, and obsessive-compulsive disorder (OCD) among children during the 1st year of the COVID-19 pandemic.MethodsA longitudinal study with three cross-sectional timepoints [April 2020 (n = 273), October 2020 (n = 180), and April 2021 (n = 116)] was conducted at a K-12 public school in Florida. Infection and sero-positivity for SARS-CoV-2 was determined by molecular and serologic approaches. Adjusted odds ratios using mixed effect log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Despite being the least cited factors in this theme, with only one mention each, the roles of race, education, and personal beliefs and attitudes cannot be understated. Racial background significantly increased the risk of OCD among non-White participants compared to their white counterparts [49]. The prevalence of White students, Black students, Hispanic students, and Multiracial/Other participants were 22.8%, 50.0%, 42.9%, and 100%, respectively.…”
Section: Race Educational Attainment and Personal Beliefs And Attitudesmentioning
confidence: 95%
See 4 more Smart Citations
“…Despite being the least cited factors in this theme, with only one mention each, the roles of race, education, and personal beliefs and attitudes cannot be understated. Racial background significantly increased the risk of OCD among non-White participants compared to their white counterparts [49]. The prevalence of White students, Black students, Hispanic students, and Multiracial/Other participants were 22.8%, 50.0%, 42.9%, and 100%, respectively.…”
Section: Race Educational Attainment and Personal Beliefs And Attitudesmentioning
confidence: 95%
“…Diagnosis of relatives and family members with COVID-19 was also a highly cited (4) factor shaping OCD outcomes among children and adolescents. All the studies unequivocally reported a significant association between participants' adverse OCD outcomes and diagnoses of relatives and family members [4,34,36,49]. OCD was associated with participants who lost a family member due to COVID-19 [50].…”
Section: Death or Diagnosis Of Relatives And Family Members From Covi...mentioning
confidence: 99%
See 3 more Smart Citations